Diseño de señalética digital en el campus Salache, sector casa hacienda de la Universidad Técnica de Cotopaxi - Tigse Espinosa, Kevin Francisco (2023)
The current research work analyzes the topic "Digital signage design at the Salache campus, Casa Hacienda sector front Cotopaxi Technical University, which has been raised against the existing problem, where the signage in places, what are intended to develop tourist activities is nil, this negatively affects external visitors to the institution, as well as students from tourism career, since these spaces are used to complement their training, tor this reason, it has been considered as a general aim to design digital signage, by tools techniques and research for its subsequent implementation at the Salache campus, Casa Hacienda Sector. The current research works based on the qualitative approach guidelines, using the descriptive methodology, by fact virtue, what it is sought the digital signage execution and verification as a communication tool within the tourist activity from Salache campus, for the effect it was used the bibliographical research technique and observation, whose captured results into digital signage designs to ensure stated aim compliance, the activities focused onto diagnosing the study area, by primary and secondary research sources, making digital signage schemes, through technical design tools, applying QR codes at strategic points for the pro,•ct verification; once, it has been completed these research stages, it has been established as the main conclusion, what thanks to the QR Codes application, lt was achieved to give access to the signage to all students, who perform their activities at the Salache campus, as well as external visitors to the institution, this way, it was verified the project functionality, digital signage implementation part is to share the content an auditory and visual way, by covering in a second language for a more accessible environment.